Mapping the learning styles of medical students in Brazil - Cardozo, Marcel Fernando Inácio; de Jesus, Gilmar Cardozo; de Sousa, Maria Helena; Iatecola, Amilton; Melgaço Maia, Fernanda Latorre; de Carvalho, Gisele Massarani Alexandre; Silva, Vinícius Rodrigues; Buchaim, Daniela Vieira; Moura Cardozo, Adriane Gonçalves; Correia, Ronny Rodrigues [UNESP]; Buchaim, Rogerio Leone; da Cunha, Marcelo Rodrigues (Springer Nature, 2024)
Background: Medical education has evolved based on the application of pedagogical actions that place the student as the protagonist of the learning process through the use of active teaching methodologies. Within this context, higher education teachers should use strategies that focus on the student and his/her context and avoid traditional teaching methods. Specifically in medical schools, there is an even greater challenge since the teaching methods of medical curricula differ from those used in previous schooling. Consequently, students acquire their own style of processing information that is often incompatible with the profile of medical schools. This may be one of the factors responsible for the lack of motivation among undergraduates. Objective: The aim of this study was to characterize the learning styles of students enrolled in a Brazilian medical school using the Felder-Soloman Index of Learning Styles (ILS). Methods: This was a cross-sectional, descriptive, quantitative study that included students from the 1st to the 6th year of a Brazilian medical school. The students participating in this study voluntarily answered 44 questions about learning styles of the Felder-Silverman instrument validated in Brazil. The instrument was divided so that each domain consisted of 11 questions with two response options in which only one could be selected. For each domain, a score (1 point) was assigned to the selected option (a, b) of the question and the learning style category was determined as the difference between these values. For data collection and tabulation, we used the Learning Syle Platform (EdA Platform) developed based on Felder’s studies since this system processes information about the dimension analyzed, the preferred style, and the most striking characteristics of each style. Results: The results showed that sensing was the preferred learning style of the students, followed by the sequential and visual styles. It was not possible to determine whether gender or age influences the choice of learning methods because of the homogeneity of the results. Conclusions: The present data will enable teachers of the institution involved in this study to plan pedagogical actions that improve the students’ self-awareness, as well as their teaching-learning skills, by choosing the most adequate active methodologies for the medical education programs considering the individuality of each student and class.
Keywords: Learning; Learning styles; Medical education; Teaching; Teaching methods